Perancangan Aplikasi Pelaporan Tempat Sampah Liar dengan Integrasi Peta Interaktif Menggunakan Metode Rapid Application Development - Affan, M Zafid; Handayani, Irma (TIN: Terapan Informatika Nusantara, 2025)
This study discusses the design of a digital application for reporting illegal waste disposal sites with interactive map integration as a solution to urban waste management issues. Before the implementation of the digital system, reporting was conducted manually, where citizens had to upload photos of illegal waste sites to the Google Drive managed by the Environmental Agency (DLH), and admins verified each report individually while coordinating with field officers manually. This process caused delays in follow-up actions, duplicate reports, and lacked a structured database of illegal waste locations. The system was developed using the Rapid Application Development (RAD) methodology, which allows iterative and flexible processes based on user needs. Data were collected through interviews with DLH officials and field observations to map the reporting workflow of illegal waste disposal sites. The system consists of two platforms: a mobile application for citizens (reporters) and field officers, and a web dashboard for DLH admins. The mobile application for citizens allows reporting illegal waste sites with photos, descriptions, and coordinates through OpenStreetMap integration. The mobile application for field officers receives tasks from admins and monitors the handling status in real-time. The web dashboard enables admins to verify reports, assign tasks to officers, and monitor the overall handling process in real-time. Black Box Testing showed that all main features, such as user authentication, report submission, admin verification, task assignment, and submission of completion proof, functioned according to system requirements. Limited testing indicated that the implementation of the system increased reporting efficiency by 62.5% and strengthened the transparency of the reporting process. Thus, the system is considered effective in facilitating citizens to report illegal waste locations and enabling admins to monitor and follow up reports in real-time.